Crystallization and preliminary X-ray analysis of CYP153C1 from Novosphingobium aromaticivorans DSM12444. - Zhou, R; Huang, C; Zhang, A; Bell, S; Zhou, W; Wong, L (2011)
Cytochrome P450 (CYP) enzymes constitute a large family of haemoproteins that catalyze the monooxygenation of a great variety of endogenous and exogenous organic compounds. In common with other members of the CYP153 family of alkane hydroxylases, CYP153C1 from the oligotrophic bacterium Novosphingobium aromaticivorans DSM 12444 can bind linear alkanes such as heptane, octane and nonane. Here, the production, purification and crystallization of CYP153C1 and the collection of high-resolution diffraction data to 1.77 Å resolution are reported. The crystals belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 61.0, b = 96.3, c = 149.8 Å, α = β = γ = 90.0°. Preliminary X-ray diffraction data analysis revealed that the asymmetric unit is most likely to contain two protein molecules.